História e memória da Escola Complementar de Guaratinguetá (1906-1913) - Corbage, Debora Maria Nogueira (2010)
This aims to make a study of graduate students in the Complementary School of Guaratinguetá between 1906 and 1913. Investigate the first eight classes of students in order to detect its origin in the social landscapes of the city s social structure in early Republican period. For this we observe the memory build in the city of that school analyzing the Commemorative Magazines of 75 to 90 years of the school highlighting the memory written alumni and memoirs. Another important point to be investigated is in the normalistas that stood out in society were Guaratinguetá verified that the merits of these pupils economic partner